Four New Myrmecophilous Coleoptera - H. C. Fall (Psyche: A Journal of Entomology)
The following brief paper is offered primarily for the purpose of making known a most remarkable Rhyncophorous myrmecophile recently discovered in Arizona by Mr. Wm. M. Mann. Opportunity is taken however to describe three other myrmecophious novelties, two sent me by Mr. Mann, the other found by myself in California. Two of the four species are notable, in that new genera must be erected for their reception.